Artificial intelligence methods in diagnostics of coal-biomass blends co-combustion in pulverised coal burners - Smolarz, A.; Lytvynenko, V.I.; Wójcik, W.; Gromaszek, K. (Штучний інтелект, 2017)
The paper presents technologies being developed in the Institute of Electronics and Information Technologies at Lublin University of Technology. They use optical sensors and artificial intelligence methods for process supervision and diagnostics. Research is aimed to develop a system allowing a parametric evaluation of the quality of pulverized coal burner operation. Due to the highly nonlinear nature of dependencies and lack of an analytical model, the artificial intelligence methods were used to estimate and classify the selected parameter, including a relatively new class of classification methods – artificial immunology algorithms. The article shows results for coal-shredded straw blends, yet the methodology may be applied for other types of blends. У роботі представлені технології, розроблені в Інституті електроніки та інформаційних технологій Люблінського технологічного університету. Вони використовують оптичні датчики та методи штучного інтелекту для контролю та діагностики процесу. Дослідження спрямовано на розробку системи, що дозволяє провести параметричну оцінку якості роботи пиловугільного пальника. Через високу нелінійну природу залежностей та відсутність аналітичної моделі для оцінки та класифікації обраного параметра були використані методи штучного інтелекту, включаючи відносно новий клас методів класифікації - алгоритми штучної імунології. У статті наведені результати для солом'яно-вугільних сумішей, але методологія може застосовуватися і для інших типів сумішей.